170k views
2 votes
7+5(x-3)=7(x+2) Find the solution with the work shown please.

2 Answers

1 vote

Answer:

12

Explanation:

i really don't know

User Sachacr
by
5.0k points
4 votes

Answer:

x=−11

Explanation:

7+5(x−3)=7(x+2)

Step 1: Simplify both sides of the equation.

7+5(x−3)=7(x+2)

7+(5)(x)+(5)(−3)=(7)(x)+(7)(2)(Distribute)

7+5x+−15=7x+14

(5x)+(7+−15)=7x+14(Combine Like Terms)

5x+−8=7x+14

5x−8=7x+14

Step 2: Subtract 7x from both sides.

5x−8−7x=7x+14−7x

−2x−8=14

Step 3: Add 8 to both sides.

−2x−8+8=14+8

−2x=22

Step 4: Divide both sides by -2.

−2x

−2

=

22

−2

x=−11

User Ian Johnson
by
4.6k points